(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
In today’s world, many students have difficulty going to school because of their heavy bags. Thus, the researchers decided to build a multipurpose chair to help students with heavy bags, especially those living far from the school. This multipurpose chair is available for grad school, high school, and college students. The multipurpose chair has benefits for parents because it reduces their children’s anxiety over the many school items their child brings to school. the multipurpose chair will also benefit the students. Therefore, the result of this study will help the parents and students to solve their problems. A purposive sampling technique was used to choose respondents. Using a questionnaire, the researchers conducted a survey to determine whether the proposed project is acceptable in terms of concept, feasibility, construction materials, and presentation. The results of the study in terms of concept, feasibility, construction materials, and presentation are highly acceptable, as assessed by STEM teachers and students of Bestlink College of the Philippines. Results indicated no significant difference between the assessments of the two groups of respondents in terms of the cited variables. Meanwhile, the STEM teachers obtained an overall weighted mean of 4.25, which was interpreted as highly acceptable with a variance of 0.0119. Meanwhile, the STEM students obtained an overall weighted mean of 4.21, which was interpreted as highly acceptable with a variance of 0.0034. Both groups had a t-computed value of 0.66 and a degree of freedom of 18 with a value of 1.73. The t-computed values of both groups were also larger than the t-critical ones. As a result, the assessments of the two groups of respondents were accepted. The subsequent discussions forwarded by the two groups of respondents are as follows: use fly wood, cutter, stikwel, wood, shoe glue, sandpaper, nail hammer, and varnish; refer to different laws, design guidelines, and construction codes that apply to the miniature; and researchers have to pay time on the design and cabinets to improve the project.